Hubungan Antara Konsep Diri dengan Kecemasan Sosial pada Narapidana Pria Kasus Narkotika di Lembaga Permasyarakatan Kelas II A Padang - Rio Andika Putra; Poppy Febri Dina Adli (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to determine the relationship between self-concept and social anxiety in male prisoners of narcotics cases in Padang Class II A Correctional Institution. The independent variables in this study are self concept and the dependent variable is social anxiety. The measuring instruments used in this study are self concept scale and social anxiety scale. The sampling technique in this study used a simple random sampling technique. The sample in this study were 84 male prisoners of narcotics cases at the Padang Class II A Correctional Institution. Test for validity and reliability in this study using thetechnique Cronbach Alpha. The results of the validity coefficient on the self-concept scale move from rix = 0.310 to rix = 0.779 with a reliability coefficient of α = 0.944 while on the social anxiety scale moves from rix = 0.340 to rix = 0.847 with a reliability coefficient of α = 0.945 . Based on data analysis, the correlation value is -0.567 with a significance level of 0.000, which means the hypothesis is accepted. This shows that there is a significant relationship between self concept and social anxiety in male prisoners of narcotics cases at the Padang Class II A Correctional Institution.